2018
DOI: 10.21608/msnj.2018.187745
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Knowledge and Attitude Regarding Neonatal Hyperbilirubinemia

Abstract: Background: Hyperbilirubinemia is the most common problem in the newborn period that requiring hospitalization and medical attention. Approximately 60% of all newborns develop some degree of jaundice in the first week of life. Aim of the study: To assess mothers' knowledge and attitude regarding neonatal hyperbilirubinemia. Research design: A descriptive exploratory research design was used to achieve the aim of this study. Sample: A convenient sample of 375 mothers admitted to postpartum unit at Minia Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…This is expected that mothers who have a high level of education and are employed were more likely to have many sources of information than others and the level of information was increased with increasing levels of education and occupation. This finding is similar to (27) who reported that there were significant relationships between occupation and level of education with their knowledge at p-value < 0.05. and also, this finding is similar to the study of (28) who reported that there was a significant relationship between the level of education and mothers' knowledge of neonatal jaundice p= 0.020 at p-value < 0.05…”
Section: Discussionsupporting
confidence: 90%
“…This is expected that mothers who have a high level of education and are employed were more likely to have many sources of information than others and the level of information was increased with increasing levels of education and occupation. This finding is similar to (27) who reported that there were significant relationships between occupation and level of education with their knowledge at p-value < 0.05. and also, this finding is similar to the study of (28) who reported that there was a significant relationship between the level of education and mothers' knowledge of neonatal jaundice p= 0.020 at p-value < 0.05…”
Section: Discussionsupporting
confidence: 90%